Stomatal conductance of semi-natural Mediterranean grasslands: implications for the development of ozone critical levels. - Alonso, R; Bermejo, V; Sanz, J; Valls, B; Elvira, S; Gimeno, B S (Environmental pollution (Barking, Essex : 1987), 2007)
Intra-genus and intra-specific variation and the influence of nitrogen enrichment on net assimilation and stomatal conductance of some annual Trifolium species of Mediterranean dehesa grasslands were assessed under experimental conditions. Also gas exchange rates were compared between some Leguminosae and Poaceae species growing in the field in a dehesa ecosystem in central Spain. The results showed that the previously reported different O3 sensitivity of some Trifolium species growing in pots does not seem to be related to different maximum g(s) values. In addition, no clear differences on gas exchange rates could be attributed to Leguminosae and Poaceae families growing in the field, with intra-genus variation being more important than differences found between families. Further studies are needed to increase the database for developing a flux-based approach for setting O3 critical levels for semi-natural Mediterranean species.
Keywords: Critical levels; Grasslands; Ozone; Semi-natural vegetation; Stomatal conductance

Growth response to ozone of annual species from Mediterranean pastures. - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Elvira, S (Environmental pollution (Barking, Essex : 1987), 2004)
Ozone (O3) phytotoxicity has been reported on a wide range of plant species. However, scarce information has been provided regarding the sensitivity of semi-natural grassland species, especially those from dehesa Mediterranean grasslands, in spite of their great biological diversity and the high O3 levels recorded in the region. A screening study was carried out in open-top chambers (OTCs) to assess the O3-sensitivity of representative therophytes of these ecosystems based on the response of selected growth-related parameters. Three O3 treatments and 3 OTCs per treatment were used. Legume species were very sensitive to O3, because 78% of the tested species showed detrimental effects on their total biomass relative growth rate (RGR) following their exposure to O3. The Trifolium genus was particularly sensitive showing O3-induced adverse effects on most of the assessed parameters. Gramineae plants were less sensitive than Leguminosae species because detrimental effects on total biomass RGR were only observed in 14% of the assessed species. No relationship was found between relative growth rates when growing in clean air and O3 susceptibility. The implications of these effects on the performance of dehesa acidic grasslands and on the definition of ozone critical levels for the protection of semi-natural vegetation are discussed.
Keywords: Critical levels; Dehesa; Relative growth rate; Screening; Therophytes